Non-universal suffrage : measuring electoral inclusion in contemporary democracies - Schmid, Samuel; Piccoli, Lorenzo; Arrighi de Casanova, Jean-Thomas (My University, 2019)
The electoral franchise has become more universal as restrictions based on criteria such as sex or property have been lifted throughout the process of democratisation. Yet, a broad range of exclusions has persisted to this date, making the suffrage non-universal, even in established democracies. In this article, we present ELECLAW, a new set of indicators that captures the subtle and variegated legal landscape of persisting electoral rights restrictions. We measure the inclusiveness of the right to vote and the right to stand as candidate across four levels and three types of elections for three categories of voters: citizen residents, non-citizen residents, and non-resident citizens. ELECLAW currently covers fifty-one democracies in three different continents (the Americas, Europe, and Oceania) depicting the legal situation in 2015. The article introduces the methodology used for building the indicators so as to make it transparent to the broader research community. To this aim, it successively unpacks the conceptualisation underlying the indicators, explains the measurement by providing specific examples, and discusses the merits of a differentiated and context-driven method of aggregation.
Keywords: Voting rights · Candidacy rights · Citizenship · Elections · Democracy measurement · Index building